2015
DOI: 10.1007/s00392-015-0876-6
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation and hypertrophic cardiomyopathy: who to anticoagulate?

Abstract: Hypertrophic cardiomyopathy (HCM) is one of the most common genetic cardiac conditions. Atrial fibrillation (AF) has been demonstrated to be the most frequent arrhythmia encountered in HCM patients. Research focusing on AF and embolic stroke in HCM patients has been sparse and the sample size of most studies is small. The prognostic significance of AF in HCM patients is still not well known. The aim of this article is to provide further understanding of the anti-coagulation requirement of HCM patients with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The development of AF has a direct impact on morbidity and mortality, as demonstrated by Olivotto et al, who reported that patients with AF had an increased risk of hospitalizations and mortality related to heart failure and cardioembolic events . Our study showed that thromboembolic complications occurred despite the use of anticoagulation therapy; however, some of them were out of therapeutic range, suggesting that this group of patients requires stricter anticoagulation follow‐up …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The development of AF has a direct impact on morbidity and mortality, as demonstrated by Olivotto et al, who reported that patients with AF had an increased risk of hospitalizations and mortality related to heart failure and cardioembolic events . Our study showed that thromboembolic complications occurred despite the use of anticoagulation therapy; however, some of them were out of therapeutic range, suggesting that this group of patients requires stricter anticoagulation follow‐up …”
Section: Discussionsupporting
confidence: 56%
“…14 Our study showed that thromboembolic complications occurred despite the use of anticoagulation therapy; however, some of them were out of F I G U R E 3 Example of a patient that did not develop AF therapeutic range, suggesting that this group of patients requires stricter anticoagulation follow-up. 12,15 Several studies demonstrated an acceptable correlation between the E/e′ ratio and the filling pressures estimated by invasive methods, and with the functional capacity evaluated by clinical assessment or determination of oxygen uptake. 10 E/e′ ratio is influenced by outflow tract gradient, mitral regurgitation, septal, or lateral fibrosis; among others.…”
Section: Discussionmentioning
confidence: 99%
“…1 Given the high thromboembolic risk in HCM patients with concomitant AF, life-long oral anticoagulation is recommended, regardless of the CHA 2 DS 2 VASc score. [2][3][4] Non-vitamin K anticoagulants (NOACs) have emerged as a valid and more practical alternative to vitamin K antagonists (VKAs). 5,6 Even though data supporting the use of NOACs in patients with HCM and AF are sparse, recent observational studies suggest that NOACs might be safely used in this population.…”
Section: Introductionmentioning
confidence: 99%
“…AF is a common sequela for patients with HCM and associated with worse symptoms and exercise capacity, and a significantly higher risk of heart failure related mortality and embolic stroke [1,8,9,12,15]. Substantial studies have demonstrated aging and left atrial enlargement were closely related with susceptibility to AF in HCM [1,7,9,12,15,16]. Aging is an unmodifiable factor, but left atrial enlargement is not.…”
Section: Discussionmentioning
confidence: 99%
“…With an estimated prevalence of 20%, atrial fibrillation is the most common arrhythmia in patients with HCM, potentially increasing the risk of embolic stroke and aggravating progressive heart failure [1,[7][8][9]. Therefore, early recognition of predisposing factors to AF has important implications for longitudinal surveillance and timely prophylactic interventions and management strategies in patients with HCM.…”
Section: Introductionmentioning
confidence: 99%